Exploration on perception o suicidal ideation among students of Higher Institutions - Jusnani, Embing; Salmah, Mohamad Yusoff; Mohd Razali, Bin Othman (UNIMAS Publisher, 2020)
Suicide is one of the top causes of death worldwide among youth aged 15-29 years. Students of higher institutions are also involved in the specific group that was reported to have a high level of suicidal ideation. Thus, in order to overcome this issue, all factors that influence suicidal ideation should be identified. This study is intended to identify the factor that influences suicidal ideation among higher learning education students based on their perceptions This study was conducted using a qualitative method using semi-structured interview questions to explore participants’ perceptions towards suicidal ideation among students of higher learning institutions. Two focus group discussions were chosen as the method for data collection. The data in this study were analyzed using thematic analysis method. Specifically, data analysis uses thematic analysis based on six simple steps introduced by Braun and Clarke (2006). The findings show that the participants have an understanding of suicidal ideation. Factors identified to influence the existence of suicidal ideation among students of higher learning institutions can be categorized into two categories, external factors, and internal factors. These factors are peer pressure, pressure from society, social media influences, family factors, financial factors, intrapersonal and individual interpersonal factors, and low self-esteem factor. This study also found that many participants agreed that person internal factors are the most dominant factors affecting suicidal ideation. This study also found that counsellors and other professional bodies such as psychologists were not the choices of participants to express a problem that led to their suicidal ideation.